Efficacy of the staged endoscopic ligature of the varicose veins in children, suffering portal hypertension - D. I. Voroniak; O. S. Godik; I. V. Kolomoiets; O. G. Dubrovin (Клінічна хірургія)
Objective. To estimate the efficacy of first procedure of endoscopic ligature for the varicose esophageal veins in children, suffering portal hypertension in accordance to data of endoscopic examination.